2018 IEEE Symposium on Visualization for Cyber Security (VizSec) 2018
DOI: 10.1109/vizsec.2018.8709230
|View full text |Cite
|
Sign up to set email alerts
|

Eventpad: Rapid Malware Analysis and Reverse Engineering using Visual Analytics

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 18 publications
0
20
0
1
Order By: Relevance
“…More recent works try to reduce the effort involved during manual labeling through the use of visualization tools. In particular, the use of visual systems help user during labeling by improving correlation between malicious patterns and making the user more confident about their labels [68].…”
Section: Manualmentioning
confidence: 99%
“…More recent works try to reduce the effort involved during manual labeling through the use of visualization tools. In particular, the use of visual systems help user during labeling by improving correlation between malicious patterns and making the user more confident about their labels [68].…”
Section: Manualmentioning
confidence: 99%
“…While not being in the focus of this project, we found that our query definition interface lacks the option to define pattern sequences across tracks. We plan to investigate better query interfaces for MTS data following recent examples, such as [16].…”
Section: Interactive and Transparent Visual Interface For Multivariat...mentioning
confidence: 99%
“…Another approach for forensic analyses of malware was introduced with Eventpad [4]. Eventpad's advantage is its capability to significantly reduce the complexity within network traffic samples to quickly understand the networking behavior of malware samples.…”
Section: Related Workmentioning
confidence: 99%
“…Before we explicitly discuss the individual steps of the pipeline within our prototype, we briefly describe its overall structure. It is designed as a client 4 -server 5 application with an underlying document-oriented database 6 for persisting the raw data acquired from the Data Collection and the pre-processed data. The pre-processed data is the output of the Data Analysis step, in which a Python script continuously prepares newly available raw data.…”
Section: Research Prototypementioning
confidence: 99%